2019
DOI: 10.1007/978-3-030-31635-8_193
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of a Whole Surgical Tool Within Safe Regions Utilizing Barrier Artificial Potentials

Abstract: Active constraint enforcement in robotic-assisted surgery is critical for reducing the intra-operative risk of unintentionally damaging sensitive tissues by the surgical instrument. This work considers surgical instruments which can be circumscribed by a geometric capsule and forbidden regions which can be approximated by point clouds in order to produce a repulsive wrench by the control action to guarantee manipulation within safe regions. This work details the control scheme which is based on barrier artific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 9 publications
0
26
0
Order By: Relevance
“…Finalizing, we emphasize the significance of all digital technologies in the field of education and the positive impact on teachers, which is highly effective and productive for assessment, intervention, and educational procedures via mobile devices that bring educational activities to everybody [42][43][44][45][46][47][48][49], various ICTs applications that are the main supporters of education [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65], AI, STEM, and ROBOTICS that raise educational procedures to new performance levers [66][67][68][69][70][71][72][73][74][75][76][77], and games which support a very friendly and enjoyable procedure in the education [78][79][80][81][82][83][84]. Additionally, the integration of ICTs with theories and models of metacognition, mindfulness, meditation, and the cultivation of emotional intelligence , as well as with nutrition and environmental factors…”
Section: Discussionmentioning
confidence: 99%
“…Finalizing, we emphasize the significance of all digital technologies in the field of education and the positive impact on teachers, which is highly effective and productive for assessment, intervention, and educational procedures via mobile devices that bring educational activities to everybody [42][43][44][45][46][47][48][49], various ICTs applications that are the main supporters of education [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65], AI, STEM, and ROBOTICS that raise educational procedures to new performance levers [66][67][68][69][70][71][72][73][74][75][76][77], and games which support a very friendly and enjoyable procedure in the education [78][79][80][81][82][83][84]. Additionally, the integration of ICTs with theories and models of metacognition, mindfulness, meditation, and the cultivation of emotional intelligence , as well as with nutrition and environmental factors…”
Section: Discussionmentioning
confidence: 99%
“…For example, penetrated (bounded) artificial potentials are utilized around trajectories encoded by Dynamic Movement Primitives to allow a user to inspect kinesthetically as well as significantly modify a previously learned path [7,8]. A method enforcing constraints utilizing unbounded functions are presented in [9] and [33] to guarantee that the robot tool tip and the whole tool respectively will never touch a forbidden surface provided by a point cloud. A review about artificial potential fields can be found in [34].…”
Section: Related Workmentioning
confidence: 99%
“…In this work, we address the problem of satisfying both RCM and forbidden region constraints via a novel admittance control design. A combination of our previous works [14] on RCM constraint and forbidden region constraint satisfaction [9], [33] produces a system that is not passive and consequently it cannot guarantee stability. In fact, we faced various stability problems when we had initially experimented with this control combination.…”
Section: Contributionsmentioning
confidence: 99%
See 2 more Smart Citations